352 уже кто-то сделал
Пошаговое объяснение:
- функция убывает при х ∈ ( - ∞; -1) ∪ (0 ; 1);
- функция возрастает при х ∈ (-1; 0) ∪ (1; +∞).
Пошаговое объяснение:
y = x ^ 4 - 2 * x ^ 2 + 1
y ` = 4 * x ^ 3 - 4 * x
y ` = 0, 4 * x ^ 3 - 4 * x = 0
4 * x * (x ^ 2 -1) = 0
4 * x = 0 x ^ 2 - 1 = 0
x = 0 x ^ 2 = 1
x = ± 1
x = - 1 x = 1
Отметим на координатной прямой эти точки и промежутки:
- функция убывает при х ∈ ( - ∞; -1) ∪ (0 ; 1);
- функция возрастает при х ∈ (-1; 0) ∪ (1; +∞).
350. 1) а)3/4 б)2/6 в)5/8 г)4/7
2) а)1/4 б)4/6 в)3/8 г)3/7
352. 1) 32 : 8 = 4
4х3=12
ответ: 12
2) 48:12=4
4х7=28